Maternal Age at Delivery and Enzyme Polymorphisms in Children with Type 1 Diabetes Mellitus - Gloria-Bottini, Fulvia; Neri, Anna; Saccucci, Patrizia; Manca Bitti, Maria Luisa; Rapini, Novella; Renzetti, Gabriele; Magrini, Andrea; Bottini, Egidio (Journal of Child Science, 2018)
Fetal genetic adaptation to environment of aging women could result in positive selection of genes that during extrauterine life increases the risk of type 1 diabetes mellitus (T1DM). We have examined the distribution of three genetic polymorphisms (acid phosphatase locus 1 [ACP1], p53 codon 72, and PTPN22) involved in T1DM risk in relation to maternal age at delivery. p53 codon 72 was determined in 281 T1DM children, ACP1 in 207 children, and PTPN22 in 216 children. Controls (blood donors) were 351 for ACP1, 271 for PTPN22, and 730 for p53 codon 72. Genotypes were determined by DNA analysis. The proportions of the three genotypes associated with T1DM are much greater in T1DM children from older mothers than in those from young mothers and in controls. The data support the hypothesis that advanced maternal age favors a positive selection of genes more adapted to the uterine environment of older women: these genes predispose to T1DM during extrauterine life.
Keywords: ACP1; maternal age; p53 codon 72; PTPN22; type 1 diabetes mellitus